Intensive care unit dignified care: Persian translation and psychometric evaluation - Amir Jalali; Niloufar Darvishi; Parnia Kalhory; Fateme Merati; Salam Vatandost; Khalil Moradi (Nursing Open, 2024)
Abstract Aim The present study aimed to evaluate the psychometric properties of the Persian version of the ‘Intensive Care Unit Dignified Care Questionnaire (IDCQ)’ among Iranian nurses. Design A methodological and psychometric study was conducted in 2022, involving nurses from six teaching hospitals in Kermanshah, Western Iran. Methods The IDCQ was translated into Persian using a forward‐backward translation method. Construct validity was assessed through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), employing a stratified sampling method with 455 critical care nurses. Internal consistency was gauged using Cronbach's alpha coefficient, while reliability was determined through the test–retest method. Analyses were performed using SPSS version 26 and Lisrel version 8 software. Results EFA and CFA validated the instrument's two‐factor, 17‐item structure. The CFA indicated a well‐fitting model with fit indices: CFI = 0.93, NNFI = 0.92, GFI = 0.861, RMSEA = 0.051 and SRMR = 0.046. Pearson's correlation coefficient substantiated a significant relationship between the items, subscales and the overall scale. The instrument's reliability was confirmed by a Cronbach's α coefficient of 0.88 and a test–retest reliability of 0.86. Conclusion The Persian version of the IDCQ, comprising two factors and 17 items, has been validated as a reliable and applicable tool for use within the Iranian nursing community.